Investigation of complex eigenvalues for a stationary problem with two-point nonlocal boundary condition - Skučaitė-Bingelė, Kristina; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2011)
The Sturm–Liouville problem with one classical and another two-point nonlocal boundary condition is considered in this paper. These problems with nonlocal boundary condition are not self-adjoint, so the spectrum has complex points. We investigate how the spectrum in the complex plane of these problems (and for the Finite-Difference Schemes) depends on parameters γ and ξ of the nonlocal boundary conditions.